INTEGRATION OF IT AND FOREIGN LANGUAGE TEACHING: MODERN APPROACHES AND OPPORTUNITIES. - Solijonova Gulnozaxon Sherzodjon qizi, (Ustozlar uchun, 2025)
This article explores the integration of Information Technology (IT) and foreign language teaching methodology. In the context of globalization, learning foreign languages is unimaginable without modern technological tools. The research analyzes the effectiveness of digital resources, interactive platforms, and AI-based tools in teaching foreign languages, as well as their impact on students’ motivation and language competence. The article discusses the advantages, challenges, and prospects of organizing effective foreign language lessons through modern IT tools. Integration not only increases students’ interest in language learning but also develops their independent learning skills.